Short-Answer Questions


Short-Answer Questions

Solve: $x^{2}+5 x-\left(a^{2}+a-6\right)=0$


$x^{2}+5 x-\left(a^{2}+a-6\right)=0$

$\Rightarrow x^{2}+5 x-(a+3)(a-2)=0$

$\Rightarrow x^{2}+[(a+3)-(a-2)] x-(a+3)(a-2)=0$

$\Rightarrow x^{2}+(a+3) x-(a-2) x-(a+3)(a-2)=0$

$\Rightarrow x[x+(a+3)]-(a-2)[x+(a+3)]=0$


$\Rightarrow x+(a+3)=0$ or $x-(a-2)=0$

$\Rightarrow x=-(a+3)$ or $x=(a-2)$

Hence, $-(a+3)$ and $(a-2)$ are the roots of the given equation.


Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now